System Usability Scale (SUS) implementation in Ruang Baca Virtual – UT Library - Suci Ramadhani Arifin (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Universitas Terbuka (UT) implements Distance Learning and since 2012 launched Ruang Baca Virtual (RBV) application to improve student learning services and provide alternative conveniences for students to utilize teaching materials online and help other universities wish to carry out online learning as an alternative solution to face-to-face replacement lecture services. Usability is one of the key factors for successful technology adoption. During the implementation of RBV, usability testing has never been carried out. The purpose of this study was to determine student perceptions of RBV usability. RBV usability testing was carried out using the questionnaire method using the system usability scale (SUS) instrument. The test results show that a SUS score of 72,66 placing RBV in the “acceptable” range, corresponds to a grade of C and the usability of RBV can be rated as “Good”.